The Crisis of Increasing Segregation and Inequality in Antwerp. A Heterotopic Perspective as a Diaconal Response - Koivunen, Willemijn (Diaconia, 2024)
In the Belgian city Antwerp, as in many other cities in Western-Europe, we face a crisis of inequality and segregation. Those who deviate from the norm are excluded or disciplined, normalised. To address this, diaconal theologians such as Trygve Wyller, Kaia Rønsdal and Gyrid Gunnes have developed an alternative approach to view otherness. Using Michel Foucault’s concept of heterotopia, they reflect on the relation between what is considered normal and what is considered different. Heterotopias are other spaces, of a liminal or more permanent crisis of deviance. This article explores the contribution of a heterotopic approach to navigating the crisis of inequality and segregation. Experiences of otherness and strangeness at a diaconal practice for young refugees in Antwerp are interpreted, using Foucault’s heterotopology as a framework. Heterotopia is about reflecting on normal space from the other space. Therefore, as a form of collaborative ethnography, a documentary is made together with the involved youth, in order to make their point of view and their voices the focus of this research. This article demonstrates the epistemological quality of a heterotopic perspective, under the condition that it is not understood in a utopic way. The article shows that the contribution of such a perspective lies in uncovering the complex and often painful and confronting character of these other spaces; thereby exposing the excluding and disciplining mechanisms of power at play in society and in diaconal practices.